ISSUANCE OF LAND TITLE CERTIFICATES AS LEGAL CERTAINTY GUARANTEE FOR LAND TITLE HOLDERS - Prihatmaka, Wahyu; Hasnati; Yetty (International Peneliti Ekonomi, Sosial dan Teknologi, 2025)
Ownership of land that is not supported by sufficient evidentiary strength is vulnerable to unilateral claims, forced takeovers, and even criminalization of ownership. A certificate, which should serve as a legal shield for the owner, may instead become the source of disputes if the issuance process is not carried out in accordance with legal norms. In this context, the legal protection theory developed by Philipus M. Hadjon becomes relevant, which states that legal protection should not only be reactive in the event of rights violations but must also be preventive through orderly and transparent administrative systems and procedures. The objective of this research is to analyze the legal regulation of land title certificate issuance as a guarantee of legal certainty for land rights holders and to examine the legal implications of such issuance. The method employed is normative legal research. Based on the results of the study, it is found that the legal regulation regarding the issuance of land title certificates as a guarantee of legal certainty has been systematically stipulated in various laws and regulations, especially in Law Number 5 of 1960 concerning Basic Agrarian Principles (UUPA) and Government Regulation Number 24 of 1997 concerning Land Registration. The issuance of certificates is the final result of the land registration process conducted by the National Land Agency (BPN) and holds legal force as legitimate legal proof of ownership. Certificates provide both administrative and judicial legal guarantees over land owned by an individual, while simultaneously creating legal certainty and legal security in every land transaction. The legal implications of the issuance of land title certificates as a guarantee of legal certainty for landholders include, among others, that the certificate confers legitimacy of ownership to a legal subject over a specific parcel of land. The certificate serves as prima facie evidence, which places the certificate holder in a strong legal position in land disputes, unless there is compelling evidence to the contrary. However, if the certificate is legally flawed due to procedural errors, data falsification, or abuse of authority by land officials, then the certificate may be annulled based on a court decision with permanent legal force. In such cases, the consequence is the loss of ownership rights and the potential imposition of legal liability on the owner and the responsible officials, including civil and criminal accountability.